2022
DOI: 10.1038/s41378-021-00335-1
|View full text |Cite
|
Sign up to set email alerts
|

Chip-scale optical airflow sensor

Abstract: Airflow sensors are an essential component in a wide range of industrial, biomedical, and environmental applications. The development of compact devices with a fast response and wide measurement range capable of in situ airflow monitoring is highly desirable. Herein, we report a miniaturized optical airflow sensor based on a GaN chip with a flexible PDMS membrane. The compact GaN chip is responsible for light emission and photodetection. The PDMS membrane fabricated using a droplet-based molding process can ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It should be noted that achieving a uniform unit conversion across all the reviewed flowmeters is challenging due to the specifics of the interrogation methods implemented in each case. As can be seen from the table, several technologies have been implemented to realize flowmeters for accurate monitoring and measurement of gas and liquid flows, including microelectromechanical (MEMS) 29 , piezoelectric 30 , electroconductive 31 , 32 and optical 6 , 7 , 33 35 sensors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that achieving a uniform unit conversion across all the reviewed flowmeters is challenging due to the specifics of the interrogation methods implemented in each case. As can be seen from the table, several technologies have been implemented to realize flowmeters for accurate monitoring and measurement of gas and liquid flows, including microelectromechanical (MEMS) 29 , piezoelectric 30 , electroconductive 31 , 32 and optical 6 , 7 , 33 35 sensors.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from the table, several technologies have been implemented to realize flowmeters for accurate monitoring and measurement of gas and liquid flows, including microelectromechanical (MEMS) 29 , piezoelectric 30 , electroconductive 31 , 32 and optical 6 , 7 , 33 35 sensors.…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of science and technology and intelligence, all kinds of sensors, including temperature, [1,2] humidity, [3][4][5] air flow, [6][7][8][9] have developed explosively and been widely used in people's life and production, playing a crucial role in promoting social development. On the other hand, the fast-progressing society continues to throw higher demands on DOI: 10.1002/admi.202300077 sensors for better performance and applicability in harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…Farrell et al 9 realized a hot-carrier-based thermophotonic solar cell. Luo et al 10 reported a miniaturized optical airflow sensor based on a gallium nitride (GaN) chip with a flexible polydimethylsiloxane (PDMS) membrane. These studies are associated with multifunctional devices that can perform tasks such as energy storage, communication, and sensing.…”
Section: Introductionmentioning
confidence: 99%